Serbian producers and CE marking - Anđelić Slavica; Mladenović Vesna; Trišić Marko (Trendovi u Poslovanju)
This paper aims to solve the managerial dilemma and answer the question: Should we engage in the process of reaching the CE mark for products? The advantages of the CE mark are the following: all technical barriers concerning export are eliminated, there is the possibility of achieving good competitiveness in the foreign market, if the product is of high quality, there is a possibility of equal cooperation with foreign companies, greater competitiveness and the domestic market are ensured. Difficulties: confronting with a complete and consistent assessment of compliance of all product performances - the 'moment of truth', the compliance assessment costs (may be high, thus increasing product on costs), inclusion of foreign notified body (price, language of correspondence).